PENINGKATAN PEMAHAMAN PERAN KOPERASI BAGI PENGUSAHA PEMULA UMKM SETU BABAKAN DI KECAMATAN JAGAKARSA - Rambe Kamarul Zaman; Reny Andriyanty; Ahmad Nurdin Hasibuan; Asrarudin Asrarudin (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
This service program aims to assist the government's efforts in increasing public knowledge of the importance of cooperatives in developing business for novice business actors in Jagakarsa sub-district. The target audience was seventeen novice business actors in the Betawi cultural heritage Setu Babakan Srengseng Sawah Jagakarsa District, South Jakarta. The activity model was counseling combined with discussion method between the target audience and the team. The service material was directed at the use of own capital from cooperatives and using a revolving capital model. The activities carried out were able to increase the knowledge of the target community. Before the activity, the participants's understanding of the role of cooperatives as a source of shared capital was 49 percent. Based on post-activity analysis related to the level of understanding of the target community on average increased by 19 percent to 68 percent. The suggestion for this service activity is that the activity must be carried out continuously.